Skin disease in donkeys (Equus asinus): a retrospective study from four veterinary schools. Issue 3 (4th March 2019) - White, Stephen D.; Bourdeau, Patrick J.; Brément, Thomas; Vandenabeele, Sophie I.; Haspeslagh, Maarten; Bruet, Vincent; Sloet van Oldruitenborgh‐Oosterbaan, Marianne M.
Abstract : Background: Donkeys are important throughout the world as work animals and occasionally as pets or a meat source. Most descriptions of skin disease in donkeys are reported in small case series, textbooks or review articles. Hypothesis/Objectives: To document skin diseases and their prevalence in donkeys and to investigate predilections for the most common conditions. Animals: Case populations at four veterinary schools totalling 156 donkeys. Methods and materials: A retrospective study was performed by searching computerized medical records, using the key word "donkey", at the School of Veterinary Medicine, University of California, Davis (UCD). Records of donkeys from the veterinary schools in Nantes, France; Utrecht, Netherlands and Ghent, Belgium were searched in a similar manner. The time periods included in the searches varied by institution. Results: At UCD, 83 of 346 (24%) of donkeys had skin disease noted in their records. The most common diagnoses were insect bite hypersensitivity, sarcoid and habronemiasis. At Nantes, 36 of 144 (25%) had skin disease and the most common diagnoses were sarcoid and superficial pyoderma. At Utrecht 23 of 143 (16%) had skin disease and the most common diagnosis was dermatophytosis. At Ghent, 14 of 320 (4%) had skin disease and the most common diagnosis was sarcoid. Conclusions and clinical importance: Cutaneous conditions in donkeys are common. Age, sex and breed predisposition and the most common diagnoses varied with geographical location. Clinicians should include a dermatological examination regardless of the reason for presentation. Abstract : Background – Donkeys are important throughout the world as work animals and occasionally as pets or a meat source. Most descriptions of skin disease in donkeys are reported in small case series, textbooks or review articles.Hypothesis/Objectives – To document skin diseases and their prevalence in donkeys and to investigate predilections for the most common conditions.Conclusions and clinical importance – Cutaneous conditions in donkeys are common. Age, sex and breed predisposition and the most common diagnoses varied with geographical location. Clinicians should include a dermatological examination regardless of the reason for presentation.